Penyelamatan ukm dari guncangan wabah sars-cov-2: Sebuah kasus dari Samarinda, Indonesia - Wijaya, Adi; Jiuhardi, Jiuhardi; Nurjanana, Nurjanana (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
Covid-19 does not only threaten the health aspect, but also threatens social tensions and the economic order. The existence of Small and Medium Enterprises (SMEs) is at the point of collapse. If it is not anticipated through comprehensive reform efforts, then the existence of SMEs is only a discourse and will slowly sink. This article aims to investigate the effects of the pandemic on the SMEs sector in Samarinda City. The method uses a qualitative-case study approach. Referring to the exploratory review, two points are concluded. First, the initial conditions (before Covid-19), the reputation of SMEs classified as "not severe" reached 92.7 percent, while only 1 percent of SMEs were "severe" and 6.3 percent "moderate". Second, after the emergence of Covid-19, there appeared to be significant changes, where there were 56.8 percent of SMEs in "severe" capacities, only a few of them were "not severe" or 15.4 percent, and 27.8 percent were "moderate". Technically, Covid-19 is a holistic cause in the decline in the growth of SMEs in Samarinda City. Additional alternatives are designed to urge and reconstruct the National Economic Recovery (PEN) through the actualization of fiscal instruments (capital assistance, tax relaxation and implementation of partnerships) for SME activists.